The Dogma of Salvation in Jesus Christ, Presented in Various Ways in Prophesying and Explained in Theology - Łukaszuk, Tadeusz (Studia Theologica Varsaviensia, 2020)
The Dogma of Salvation in Jesus Christ, Presented in Various Ways in Prophesying and Explained in Theology